2019
DOI: 10.5430/ijhe.v8n4p36
|View full text |Cite
|
Sign up to set email alerts
|

Leadership Self-Efficacy, Change Oriented Behavior and Organizational Citizenship Behavior: The Moderating Effect of Experience

Abstract: Knowledge is an essential factor in human existence. Education has been found responsible for social, economic, cultural and technological development of human society. Higher education institutions are responsible for producing required skilled human capital needed to enhance sustainable development. For these institutions to meet up with numerous demand of the society and function effectively leadership is an essential factor to be considered. This study examined the effect of leadership self-efficacy, chang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 26 publications
1
7
0
Order By: Relevance
“…Thus, the seventh hypothesis is accepted. It is known that the results of this study are in line with previous researchs which have confirmed that self-efficacy leads to OCB [ 26 , 47 , 48 ]. The results of this study indicate that officers in the seven prisons in Nusakambangan who have high self-efficacy tend to be more confident because they believe he can complete his work, then they will dare to take action and maximize their abilities, including leading to a willingness to do work outside of their obligations such as OCB.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…Thus, the seventh hypothesis is accepted. It is known that the results of this study are in line with previous researchs which have confirmed that self-efficacy leads to OCB [ 26 , 47 , 48 ]. The results of this study indicate that officers in the seven prisons in Nusakambangan who have high self-efficacy tend to be more confident because they believe he can complete his work, then they will dare to take action and maximize their abilities, including leading to a willingness to do work outside of their obligations such as OCB.…”
Section: Resultssupporting
confidence: 92%
“…Theory of JSE which is known that individuals with JSE will be able to influence the goals [ 25 ] that individuals choose for themselves; the level of commitment shown by workers to work; and attitudes toward learning and handling complex tasks [ 26 ]. In line with the COR theory, self-efficacy will act as a resource in times of organizational change, which in turn increases changes in attitudes and supportive behavior [ 14 ].…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…In a survey by Osipova and Ayupora as mentioned by Adewale, et al (2019), the level of change management awareness and the relationship between the application of the change management tool and the successful implementation of innovative processes were discussed. The survey results provided proved that there is a relationship between the two and this can be used to boost project efficiency.…”
Section: Change Managementmentioning
confidence: 99%
“…A variety of experiences are thought to influence self-efficacy beliefs including mastery experiences (previous experiences), vicarious experiences (observing others' experiences), social persuasions (influence through communications with significant others), or affective or physiological influences (Bandura, 2006). Since older directors had lower self-efficacy scores in this study, older dietetics directors may need more encouragement and reinforcement in their abilities to overcome FEM obstacles or they may be more skeptical about implementing a new program based on previous experiences (Adewale, Jamil, & Khadijah, 2019). Further research would be necessary to understand mediating variables of director self-efficacy regarding FEM implementation.…”
Section: Self-efficacymentioning
confidence: 87%